Association Between Elevated suPAR, a New Biomarker of Inflammation, and Accelerated Aging. (16th July 2020) - Rasmussen, Line Jee Hartmann; Caspi, Avshalom; Ambler, Antony; Danese, Andrea; Elliott, Maxwell; Eugen-Olsen, Jesper; Hariri, Ahmad R; Harrington, HonaLee; Houts, Renate; Poulton, Richie; Ramrakha, Sandhya; Sugden, Karen; et al.
Abstract: Background: To understand and measure the association between chronic inflammation, aging, and age-related diseases, broadly applicable standard biomarkers of systemic chronic inflammation are needed. We tested whether elevated blood levels of the emerging chronic inflammation marker soluble urokinase plasminogen activator receptor (suPAR) were associated with accelerated aging, lower functional capacity, and cognitive decline. Methods: We used data from the Dunedin Study, a population-representative 1972–1973 New Zealand birth cohort ( n = 1037) that has observed participants to age 45 years. Plasma suPAR levels were analyzed at ages 38 and 45 years. We performed regression analyses adjusted for sex, smoking, C-reactive protein, and current health conditions. Results: Of 997 still-living participants, 875 (88%) had plasma suPAR measured at age 45. Elevated suPAR was associated with accelerated pace of biological aging across multiple organ systems, older facial appearance, and with structural signs of older brain age. Moreover, participants with higher suPAR levels had greater decline in physical function and cognitive function from childhood to adulthood compared to those with lower suPAR levels. Finally, improvements in health habits between ages 38 and 45 (smoking cessation or increased physical activity) were associated with less steep increases in suPAR levels over those years. Conclusions: Our findings provide initial support for the utility of suPAR in studying the role of chronic inflammation in accelerated aging and functional decline.